“Hacia la luz de la civilización”: afrodescendientes y nación en la literatura argentina (1851-1882). "Towards the light of civilization": afrodescendants and nation in Argentine literature (1951-182) - Guevara Jaramillo, Nathalia (Latinoamérica. Revista de Estudios Latinoamericanos, 2018)
La dicotomía civilización/barbarie fue recurrente en la literatura argentina en el siglo xix; en ella, los afrodescendientes tendieron a ser ubicados del lado negativo de la ecuación, es decir, como sujetos asociados a la barbarie. En este artículo se toma como eje esta dicotomía para explorar las representaciones de los descendientes de africanos en textos literarios representativos, con el objetivo de contrastar dichas representaciones, producidas por las élites, con la obra poética de algunos autores afrodescendientes de Buenos Aires. La lectura de ambos tipos de fuentes mostrará coincidencias y diferencias en la forma de situarse en el esquema de civilización y barbarie. Abstract: The dichotomy civilization/barbarity was recurrent in 19th century Argentinian literature. People of African descent were usually placed in the negative side of the equation, that is, associated with barbarousness. In this paper this dichotomy is used as an axis for looking into representations of African descendants in representative literary works in order to set off in contrast these representations produced by the elites with the poetic works of several authors of African descent of Buenos Aires. Reading both kinds of historical sources makes it clear that they have coincidences and differences in their places in the scheme of civilization and barbarity.